Pukara de los wak’a. Cerros, muros concéntricos y divinidades tutelares en el altiplano centro-sur andino - Pablo Cruz; Richard Joffre (Journal de la Société des Américanistes)
According to information provided by colonial documentary sources, a large number of ceremonial spaces linked to the ancient cults of the tutelary wak’a were identified in different regions of the central-southern Andean highlands (Bolivia). Placed on the tops of low hills and close to the settlements, they are distinguished by a variable number of stone walls arranged in a concentric manner. Although their chronology begins in pre-Hispanic times, the majority of these sites continued to be in use in the long term. Articulating new archaeological data with historical and ethnographic information, this paper presents and analyzes different aspects of these ceremonial spaces in the Andean highlands.